Analytical Study of the Development of Islamic Law in Indonesia - Hazanah, Natriani; Netti, Misra; Aryanti, Yosi (Sekolah Tinggi Agama Islam Solok Nan Indah, 2023)
The study of Islamic law is currently experiencing development, because the impact of developments in science and technology, especially information and communication technology, is taking place rapidly. Changes in society in one place quickly spread to people in other places. The events occurring at this time stimulated the emergence of movements demanding free forms of the Quran and the Prophet's Sunnah, the reopening of the doors of ijtihad, and the abandonment of the doctrine of taqlid. This study uses a qualitative method with content analysis approach, all data taken from various sources are derived from classical holy books, books, theories and expert opinion of Islamic education. The results of this research found the results of the development of Islamic studies during colonial rule, Islamic law in Indonesia during the period of national independence and types of Islamic law and their application. Methods for updating Islamic family law include: Takhshish al-qadha', giving authority to judges, Takhayyur, choosing between opinions within one dominant school, or among four schools, even outside the Sunni school, Re-translating verses of the Quran an and Hadith (retranslation), Siyasah syar'iyyah, determining law based on benefits, Judge's Decision.